Experimental and numerical simulation research on the mechanical properties and failure characteristics of joint limestone under triaxial compression - Xiaolin Tan; Bin Du; Mingxuan Shen; Yukun Li; Gang Jiang; Xiaoyong Tang (Scientific Reports)
Abstract The anisotropic mechanical attributes and failure characteristics of jointed rock masses markedly impact the load-bearing capacity and enduring stability of engineering infrastructures. This study examines complete limestone and fractured limestone with varying joint connectivities (20%, 40%, and 60%) and joint dip angles (0°, 30°, 60°, and 90°). The impact of joint connectivity and joint dip angle on the mechanical properties and failure modes is assessed via conventional triaxial compression tests and finite difference numerical simulation methods. These findings reveal that jointed limestone has pronounced anisotropic mechanical properties. As the joint connectivity increases, the mechanical parameters of limestone generally decrease. The peak strength and peak strain of the limestone samples display a V-shaped trend as the joint inclination increases, whereas the elastic modulus initially increases, then decreases, and finally increases again. A comparison of the effects of joint connectivity and joint dip angle on the peak strength, peak strain, and elastic modulus of limestone reveals that joint connectivity has a more significant influence. Joint limestone failure primarily originates from the joint tip, with limestone samples having joint connectivities of 20%, 40%, and 60% and joint inclinations of 0°, 30°, and 60°, respectively, predominantly exhibiting characteristics of tensile shear composite failure. In contrast, intact limestone samples and limestone samples with a joint inclination angle of 90° demonstrate more shear failure characteristics. These results offer valuable insights for jointed rock mass engineering.